INNOVATION AND RESILIENCE OF MANUFACTURING FIRMS IN NIGERIA: A STUDY OF BOTTLING COMPANIES IN BENIN CITY (American Journal of Business Management, Economics and Banking, 2023)
This study investigated the impact of innovation, specifically focusing on supply chain management, on the resilience of selected manufacturing firms in Nigeria, with a particular emphasis on 7UP Bottling Company and Nigerian Bottling Company (NBC), Benin City, Edo State, Nigeria. The study explored the relationship between supply chain management practices and risk management strategies within the context of organizational resilience. Data was collected from 212 participants, consisting of 96 employees from 7UP Bottling Company and 116 from Nigerian Bottling Company. Descriptive statistics, including mean and standard deviation, were employed to analyze the characteristics of the variables, while correlation analysis was used to determine the relationship between supply chain management and risk management. The findings revealed a positive and significant correlation between supply chain management practices and risk management strategies, emphasizing the critical role of efficient supply chain management in bolstering organizational resilience. These results contribute to the existing body of knowledge and provide valuable insights for manufacturing firms in Nigeria seeking to enhance their resilience in an increasingly complex business environment.